2021
DOI: 10.3988/jcn.2021.17.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Treatment with Vagus Nerve Stimulation on Mood and Quality of Life in Korean Patients with Drug-Resistant Epilepsy

Abstract: Background and Purpose This study aimed to determine the long-term effects of vagus nerve stimulation (VNS) treatment on suicidality, mood-related symptoms, and quality of life (QOL) in patients with drug-resistant epilepsy (DRE). We also investigated the relationships among these main effects, clinical characteristics, and VNS parameters. Methods Among 35 epilepsy patients who underwent VNS implantation consecutively in our epilepsy center, 25 patients were recruited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Kim et al evaluated VNS effects (on depression, anxiety and suicide) on 25 patients who underwent implantation and observed (both in seizure responders and also in non-responders) an important reduction in suicidality, depressive symptoms and an improvement in the quality of life. This improvement increased gradually over time with a considerable result at 1-2 years follow-up [25].…”
Section: General Principles Of the Device And Clinical Applicationsmentioning
confidence: 80%
“…Kim et al evaluated VNS effects (on depression, anxiety and suicide) on 25 patients who underwent implantation and observed (both in seizure responders and also in non-responders) an important reduction in suicidality, depressive symptoms and an improvement in the quality of life. This improvement increased gradually over time with a considerable result at 1-2 years follow-up [25].…”
Section: General Principles Of the Device And Clinical Applicationsmentioning
confidence: 80%
“…Finally, in a study from South Korea, Kim et al, found that VNS therapy was associated with significant improvements in measures of suicidality, depression, and QoL in 25 PWE. 83 In conclusion, while these data are based on open trials and should be interpreted with caution, it is reasonable to conclude that VNS therapy can yield improvement in seizure frequency, depressive disorders, and QoL in PWE suffering from comorbid mood disorders. The effect on seizures and mood seems to be independent…”
Section: Neuromodulationmentioning
confidence: 88%